Curved-folding-inspired deployable compliant rolling-contact element (D-CORE). (February 2016) - Nelson, Todd G.; Lang, Robert J.; Magleby, Spencer P.; Howell, Larry L.
Abstract: This work describes a deployable compliant rolling-contact element joint (D-CORE joint) that employs curved-folding origami techniques to enable transition from a flat to deployed state. These deployable joints can be manufactured from a single sheet of material. Two fundamental configurations of the D-CORE are presented. The first configuration allows for motion similar to that of a Jacob's ladder when the joint is in a planar state while achieving the motion of a CORE when in the deployed state. The second configuration constrains all degrees of freedom to create a static structure when the joint is in the planar state and allows for the motion of a CORE in the deployed state. Curved-folding origami techniques can be used with both configurations to control the cam radius and range of motion of the D-CORE. Physical models are demonstrated in Tyvek®, polycarbonate, polypropylene, and metallic glass. A deployable translating platform constructed of an inversion of the D-CORE is also shown. Graphical abstract: Highlights for the CORE paper: Curved-fold origami techniques are used to create a deployable CORE (D-CORE). Two configurations, one being metamorphic, of a D-CORE are presented. Curved-crease geometry is linked mathematically to key properties of the joint. A deployable translating platform is presented as an inversion of the D-CORE. Physical models demonstrate single-sheet manufacture, flat storage, and deployment.